Design of TPGS-functionalized Cu3BiS3 nanocrystals with strong absorption in the second near-infrared window for radiation therapy enhancement. Issue 24 (5th June 2017) - Du, Jiangfeng; Zheng, Xiaopeng; Yong, Yuan; Yu, Jie; Dong, Xinghua; Zhang, Chenyang; Zhou, Ruyi; Li, Bai; Yan, Liang; Chen, Chunying; Gu, Zhanjun; Zhao, Yuliang
Abstract : TPGS-functionalized Cu3 BiS3 NCs with strong absorbance of X-ray and NIR light were designed to synergistically enhance the efficacy of radiation therapy. Abstract : Integrating radiation therapy with high-depth photothermal therapy in the second near-infrared (NIR) window is highly required for efficient treatment of deep-seated tumor cells. Here, we constructed a multifunctional nano-theranostic with bimetallic chalcogenide nanocrystals (NCs) functionalized with amphiphilicd -α-tocopherol polyethylene glycol 1000 succinate (TPGS-Cu3 BiS3 ). Benefiting from the strong absorbance of both X-ray and NIR light in the second NIR window, TPGS-Cu3 BiS3 CNs can not only deposit more radiation dose to trigger enhanced radiation damage in vivo, but also conduct photo-induced hyperthermia for thermal ablation in the second NIR window and effective improvement of tumor oxygenation to overcome the hypoxia-associated radio-resistance of tumors. Moreover, copper ions on the surface of TPGS-Cu3 BiS3 NCs are capable of catalyzing the Fenton-like and Haber–Weiss reactions to produce highly reactive hydroxyl radicals, leading to the increase in the level of oxygen radicals and further enhance cancer cell destruction. Apart from their therapeutic application, by means of X-ray computer tomography imaging as well as multispectral optoacoustic tomography imaging, TPGS-Cu3 BiS3 NCs also have the potential as a nano-theranostic to offer remarkable therapeutic outcome for deep-seated tumor cells in imaging-guided synergistically enhanced radiation therapy.